2011
DOI: 10.1111/j.1365-4632.2010.04705.x
|View full text |Cite|
|
Sign up to set email alerts
|

Internet use by dermatology outpatients to search for health information

Abstract: A significant proportion of patients use the Internet to search for medical information. This has a positive effect on the patients' skin diseases and on their relationships with their doctors. Therefore, doctors should be more aware of the health-related information available online and should guide patients to reliable websites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 29 publications
0
21
0
6
Order By: Relevance
“…By accepting the Internet as a natural societal phenomenon, physicians could fulfill an important role as counselors. 17 One of the major concerns about cybermedicine is the quality of Internet sites, which can contain incorrect and unsubstantiated data, 18,19 in addition to the possibility that patients could make erroneous interpretations of information, with negative consequences for their health. 20 Hence, the dermatologist could help by both recommending pages of interest during the patient's visit and promoting the development of pages with highquality information by scientific societies.…”
Section: Physician Awareness Of Patients' Use Of the Internet May Be mentioning
confidence: 99%
“…By accepting the Internet as a natural societal phenomenon, physicians could fulfill an important role as counselors. 17 One of the major concerns about cybermedicine is the quality of Internet sites, which can contain incorrect and unsubstantiated data, 18,19 in addition to the possibility that patients could make erroneous interpretations of information, with negative consequences for their health. 20 Hence, the dermatologist could help by both recommending pages of interest during the patient's visit and promoting the development of pages with highquality information by scientific societies.…”
Section: Physician Awareness Of Patients' Use Of the Internet May Be mentioning
confidence: 99%
“…Previous studies showed a positive effect of internet use on dermatology outpatients [20], but we found that the internet is a new medium for those sham advertisings, with the popularization of the internet in the majority of Chinese families. Sham advertisings are deeply rooted in China and cannot be eliminated completely at once [21].…”
Section: Discussionmentioning
confidence: 71%
“…Measuring the accuracy and accessibility of medical information on the Internet remains a daunting task. Beyond the World‐Wide Web, blogs, YouTube and other video archives, social media sites, and other Internet‐based resources now contain medical information . To simplify our task, we restricted our analysis to the World‐Wide Web, and we further limited ourselves to the use of a single search engine, Google, which as of February 2012 accounts for 66.4% of all domestic searches (U.S. explicit core search market, as measured by http://comScore.com).…”
Section: Discussionmentioning
confidence: 99%